Operational Customer Relationship Management (Crm) Application To Improve Customer Satisfaction Web-Based Customer Satisfaction - Diki Robianto; Indra Kanedi; Ricky Zulfiandry (Jurnal Komputer, Informasi dan Teknologi, 2024)
The development of science in the field of computer technology and information is currently experiencing very rapid progress. Computers are a set of technologies that greatly help human work, Customer needs need to be clearly identified, as part of product development. Customer Relationship Management (CRM) is a marketing strategy that builds a close relationship between the company and its customers. Before developing a system, firstly, the writer analyzes the current system. As for now there is no Operational Customer Relationship Management (CRM) Application system to Increase Web-Based Customer Satisfaction about customer satisfaction. From the results of making the system design Operational Customer Relationship Management (CRM) Application Design to Increase Web-Based Customer Satisfaction, the following conclusions are obtained: development of the system Design of Operational Customer Relationship Management (CRM) Applications to Increase Web-Based Customer Satisfaction is used as an SPK tool. Then, the information system Designing Operational Customer Relationship Management (CRM) Applications to Increase Web-Based Customer Satisfaction is one of the right and fast information.